Teacher emotional labour, instructional strategies, and students' academic engagement: a multilevel analysis - Burić, Irena; Frenzel, Anne C. (Teachers and teaching, theory and practice, 2021)
The aim of the present study was to explore links between teachers' emotional labour, class-perceived instructional strategies and their students' self-reported academic engagement. Data on emotional labour from N = 95 high-school teachers and their students' (N = 2,111) perceptions of instructional strategies and self-reported academic engagement were analysed through doubly latent multilevel SEM. The results indicated systematic links between teachers' emotional labour strategies and class-perceived instructional strategies and student self-reported engagement. The more frequently teachers reported to hide or suppress their feelings in class, the lower was the instructional strategies as perceived by the students. Teachers' faking emotions were found to be positively linked with class-level engagement. The obtained results imply that interventions fostering teachers' emotion-regulation strategies can be very promising, as they likely are beneficial both for teacher well-being and for teaching performance.